Stability enhancement of multi-machine power systems using Ant colony optimization-based static Synchronous Compensator. (May 2020) - Kumar, Rajeev; Singh, Rajveer; Ashfaq, Haroon
Abstract: In this paper, an innovative control scheme is developed to damp the low-frequency oscillations and voltage deviations of a multi-machine power system using an Ant Colony Optimization-based Static Synchronous Compensator. The control scheme incorporates two different proportional-integral controllers to control the gate signal in the Static Synchronous Compensator. The gain parameters of which are tuned using a metaheuristic swarm-based optimization technique called Ant Colony Optimization. The test system is exposed to a three-phase, six-cycle LLL-G fault. Zero natural dampings with additional perturbations of change in the reference voltage and electric torque are considered to simulate the worst condition. The time-domain results of the rotor dynamics and deviation in generator voltage for various test cases viz. without any controller, with the Static Synchronous Compensator, and with the proposed Ant Colony Optimization-based Static Synchronous Compensator reveal the potential of the proposed controller in alleviating the overall power system oscillations.